Considerations for continuing professional development in the post-pandemic era: national experiences from psychiatry - Hazelton, Lara; Rasasingham, Rajeevan; Milliken, Heather; McNeely, Heather E; Wei, Wei; Ma, Eulaine; Mak, Christy; Connolly, Owen; Ho, Certina; Sockalingam, Sanjeev (Canadian Medical Education Journal, 2024)
Introduction: COVID-19 led to rapid innovations in continuing professional development (CPD). We surveyed Canadian Psychiatry CPD directors to understand the pandemic’s impact and to identify effective practices. Methods: In fall 2021, an online 31-item survey was created iteratively based on discussions among CPD educators and disseminated to CPD program leaders at 17 Canadian medical schools through the Council of Psychiatry Continuing Education (COPCE). We collected information on each CPD program, adaptations associated with pandemic restrictions, and intentions regarding future delivery of CPD. Results: Nine responses were received. COVID-19 led to a shift to virtual CPD delivery, with creative and transformative strategies to maintain engagement and online security. Virtual CPD was associated with an increase in attendance and decrease in costs. Many respondents anticipated that virtual or hybrid modalities would continue post-COVID-19. Conclusion: The pandemic led to a pivot to virtual delivery of Psychiatry CPD programming. Hybrid delivery will likely be the prevalent mode of future CPD programming, requiring more technological, financial, and human resources to tackle potential challenges. In times of rapid adaptation, a national network of CPD directors can provide an important venue for knowledge exchange about innovations and effective practices and build capacity of expertise.